Auditory elicitation of event related desynchronization reveals the neuronal mechanism during listening to sura fatiha recitation - Samhani, Ismail; Mohamed Faruque, Reza (2017)
Auditory stimulus produces brainwave potential variation with time in the midbrain that can be measured on the scalp through electroencephalography (EEG). This standing frequency can be intensified, reinforced and prolonged by the interaction with other waves producing brainwave entrainment. This interactional rhythm and wave correspondingly applied in cognitive rehabilitation procedures in music therapy. However, such neural synchronization with the rhythmic and melodic intonation of the Holy Quran recitation is still unclear. Emphasizing on alpha brainwave ranges at the frequency of 8 to 13Hz, we aim to learn the neural oscillations evoked by the rhythmic sound of Sura Fatiha recitation. This auditory stimulation was done on 28 normal healthy subjects in treated quiet room with dimmed light. Electrical current was measured by using the 128-electrode sensor net of EEG (Electrical Geodesics, Inc). The data was pre-processed and analyzed by Fast Fourier Transform (FFT) to yield spectrum in power (amplitude squared, µV2) in alpha frequency band by using BESA Research 6.0 software, Germany. Event Related Desynchronization (ERD) analysis was subsequently performed.Result shows that listening to Sura Fatiha elicits event related desynchronization (ERD) which pronounced as increased cortical excitability reflecting the attentive behaviour. There is general supposition that listening to Sura Fatiha recitation modulates the neuronal amplitudes referred as alpha eventrelated desynchronization.